MENINGKATKAN LEMPAR CAKRAM MELALUI MEDIA MODIFIKASI KAYU CETAK DI SDN 05 TERDUK DAMPAK - Mired, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this study was to determine whether there is an increase in the effectiveness of learning discus by using the media to print on the timber modification of the fourth grade students at SDN 05 Terduk Dampak. Forms of research is classroom action research. The subjects in this study were teachers collaborate with fifth grade students of SDN 05 Terduk Dampak as many as 29 students. Learning discus with wood molding at siswa class V give suasanan new that has never been done before, the positive impact of such students do not experience fear , feel good and appropriate to the capabilities of the students, the decision value at start prasiklus, the first cycle and the second cycle increased systematically. The first cycle of completeness by the number of 22 students (75%) and was not finished with the number 7 students (25%) Keywords: Discus Throw , Modified Wood